Analisa Elemen Fisik Pembentuk Karakter Visual Kawasan Perkampungan Nelayan Lette Makassar - Nurmiah; Moh. Eran (Universitas Muslim Indonesia, 2022)
Abstract: A fisherman's settlement is visually a settlement for the community, seen as a slum and an underdeveloped area that does not meet the ideal requirements of a technical or non-technical dwelling. This prompted the government to revitalize the area by procuring and improving existing infrastructure. Makassar City is also known as a maritime city that has a lot of potentials but is experiencing problems in the Lette area. In the revitalization of the Lette area, which the government held, the government did not create a visual character for the area which is famous for its marine life, but what happened was that the Lette area had returned to being a slum area. This has led me to conduct research on the physical elements that make up the visual character of an ideal waterfront design standard and also direct the Lette community's perception of the factors and elements that form the visual character of building mass, space, circulation, vegetation, street furniture, and activity functions. To direct the design on visual factors that quantitatively affect visual comfort. the method used in this study is a quantitative method with a rationalistic approach, using interviews, observations, and surveys. The conclusion obtained must be that there is continuity of visual elements that provide clarity of direction to create visual comfort, arrangement of visual elements of vegetation that form sequences in an area, unity of binding lines in rows of buildings contextualized by setting openings, structures, and floor heights making comfort make comfort Visually, the dominance of elements that clarify green open spaces and the arrangement of organic building growth in the area, the formation of continuity in the flow of motion and clear and regular road conditions create a visual character in the Lette area.